Role of E-leadership on Employee Engagement - Sanchari Sinha (Citakonsultindo, 2024)
Abstract Evolution in technology is changing the functionality of organizations as companies are digitally transforming their services with the intent of improving delivery, efficiency and revenue. This transformation requires an E-leader who can lead effectively through electronic and digital medium. The influence of E-leaders on employee engagement is an emerging phenomenon. Based on the relationship between technology advancement and leadership practices, the study examines the independent variables of E-leadership and its effect on employee engagement. The result from the study shows digital transformation, organizational commitment, new methods of communication and organizational agility influence E-leadership in the form of emerging technologies, organizational learning and knowledge management, communicating through digital medium, agile technological tools and human resource strategies. The findings from the study can be used by the management of organizations while setting their hiring and training agenda as well as guidelines for E-leadership practices. The research provides theoretical and practical implications for organizations to enhance employee engagement initiatives by encouraging the role of E-leaders and understanding their importance while planning their digital transformation journey. Future research is recommended by exploring additional factors and expanding the research to case study methodology or use of primary data through survey or interview approach.